Efficient IoT-based smart irrigation system using LoRaWAN for resource optimization in agriculture - Faten Ben Aicha; Imen Ayachi (Universitas Ahmad Dahlan, 2026)
The global agricultural sector faces critical challenges such as climate change, water scarcity, and inefficient irrigation practices. This paper presents an internet of things (IoT)-based smart irrigation system designed to optimize water usage and enhance agricultural productivity in Tunisia’s semi-arid regions. The proposed system integrates sensors (YL-69 soil moisture, DHT22 temperature-humidity, FC-37 rain), a STM32L072Z LRWAN1 board, and long-range wide area network (LoRaWAN) communication to transmit real-time data to a ThingPark server and MongoDB database. A mobile application developed in Flutter enables monitoring and control through manual, automated, and event-driven modes. Experimental validation demonstrates water savings and improved irrigation efficiency compared to conventional systems. Quantitative results, benchmarking, and cost-benefit analysis confirm the system’s affordability, energy sustainability, and scalability. This solution contributes to sustainable agriculture in resource-constrained environments.